Amidation of Aldehydes with Amines under Mild Conditions Using Metal‐Organic Framework Derived NiO@Ni Mott‐Schottky Catalyst. Issue 22 (7th September 2020) - Goel, Bharat; Vyas, Ved; Tripathi, Nancy; Kumar Singh, Ajit; Menezes, Prashanth W.; Indra, Arindam; Jain, Shreyans K.
Abstract: Here we report a facile method for the synthesis of nickel oxide‐nickel (NiO@Ni) Mott‐Schottky catalyst employing metal‐organic framework (MOF) as the precursor. A direct amidation protocol of aldehydes with amines has been optimized under mild conditions using NiO@Ni Mott‐Schottky catalyst and it shows far better catalytic activity than the NiO−Ni nanoparticles prepared from simple Ni 2+ salt under similar reaction conditions. The heterogeneous catalyst is robust, recyclable and efficient to provide comparable yield to costly ligand‐based homogeneous Ni catalysts. The scope of the reaction protocol has been explored with variably substituted substrates. The reaction initiates by homolytic cleavage of peroxide and proceeds through radical mechanism. Abstract : MOF derived Ni catalyst : A facile method for the synthesis of NiO@Ni Mott‐Schottky catalyst has been demonstrated employing metal‐organic framework as the precursor. This Mott‐Schottky catalyst with a semi‐metallic NiO core and metallic Ni shell promotes the amidation of aldehydes with amines. The interface formed at the heterojunction of Ni and NiO tunes the electron density around the catalytic centers and an optimized electronic environment is generated inside the catalyst to control the charge flow during catalysis.